Homosexualiteit en marxisme. - Nicolas, Jean ([S.l.] : [s.n.])
Fonds Suzan Daniel (FSD)
Artikel overgenomen uit 'De Internationale' (1980) 23
Nederlands
Monografie
Keywords: marxisme; homoseksualiteit